Archiv von: Teachers of the Arts and medicine in the Italian Universities, ca. 1350-1630 - Lines, David A. 1964- (2013)
"The files that are available on this website offer a sampling, with non-dynamic views, of a database under construction, which has as goal the registration of all recorded teachers of Arts and Medicine in Italy during the period ca. 1350-ca. 1630. I have started with the universities of Bologna, Padua, Pavia, and Florence-Pisa and have, at the moment, registered some 15,000 different appointments, with each professor's yearly teaching counting as a single appointment. The plan is to release the database, via CD-ROM, in several installments, until the project is completed."
Original-URL(s): http://www.phil-hum-ren.uni-muenchen.de/php/Lines/DocentesN.htm
Keywords: Website